2016
DOI: 10.1177/1079063214564391
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a Name? Evaluating the Effects of the “Sex Offender” Label on Public Opinions and Beliefs

Abstract: Particularly over the past two decades, the terms sex offender and juvenile sex offender (JSO) have attained increasingly common usage in media and public policy discourse. Although often applied as factual descriptors, the labels may evoke strong subconscious associations with a population commonly presumed to be compulsive, at high risk of re-offense, and resistant to rehabilitation. Such associations, in turn, may exert considerable impact on expressions of support for certain policies as well as public bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
177
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(199 citation statements)
references
References 35 publications
10
177
0
1
Order By: Relevance
“…As suggested earlier, Harris and Socia (2014) found that survey respondents asked about their support for community notification, residence restrictions, and social network bans for "sex offenders" demonstrated significantly higher levels of support for these policies than a matched group that was given a similar series of prompts using the more sanitized "people who have committed sexual offenses". They also found higher levels of support for requiring "juvenile sex offenders" to register with police, compared to "minor youth who have committed sexual offenses".…”
Section: 'Feeling First' About Sexual Offendingmentioning
confidence: 69%
See 1 more Smart Citation
“…As suggested earlier, Harris and Socia (2014) found that survey respondents asked about their support for community notification, residence restrictions, and social network bans for "sex offenders" demonstrated significantly higher levels of support for these policies than a matched group that was given a similar series of prompts using the more sanitized "people who have committed sexual offenses". They also found higher levels of support for requiring "juvenile sex offenders" to register with police, compared to "minor youth who have committed sexual offenses".…”
Section: 'Feeling First' About Sexual Offendingmentioning
confidence: 69%
“…Harris and Socia (2014) suggested that this assumed homogeneity of the sex offender population has also permeated much public opinion survey research, noting that:…”
Section: Public Support For Sexual Offender Policiesmentioning
confidence: 99%
“…In Study 2, we examined differences in attitudes and responses to sexual offenders within the context of newspaper readership. That is, we investigated further the tentative conclusions outlined earlier by both Harris and Socia (2014) and King and Roberts (2015), by looking at the potential role of emotional newspaper reporting styles in moderating responses to the 'sexual offender' label. Thus, Study 2 examined the role of the affect heuristic in guiding attitudes and perceptions about sexual offenders.…”
Section: Aims Of This Papermentioning
confidence: 99%
“…For example, Harris and Socia (2014) found that people make more punitive judgements about a case when the perpetrators are described as 'sex offenders' than 'people who have committed a crime of a sexual nature'. Imhoff (2015) found a similar trend in his data when he compared judgements about 'paedophiles' and 'people with a sexual interest in prepubescent children'.…”
mentioning
confidence: 99%
“…Someone who commits a child sexual offense can be a pedophilic or a hebophilic but does not have to be and a pedophile does have to commit a contact offence to be labelled as such. The confusion surrounding definitions of sexual violence in society may distort the issue for the general population and make it difficult to respond to as well as prevent (McCartan et al, 2015;Harris & Socia, 2015), with the label of being a sex offender having a negative impact on all offenders, especially adolescents and children (Pittman, 2013).…”
Section: Sexual Violence: Definitions and Understandingsmentioning
confidence: 99%